Return of the homebrew coder. (Economist, 2004)
Most modern software is written by huge teams of programmers. But there is still room for homebrew coders, at least in some unusual niches. The new craftsmen write software. This is because, as digital technology grows, consumers are running into problems. In many cases these programmers are making a decent living in the process, thanks to the availability of high-speed internet connections, cheap web-hosting services and online-payment systems such as PayPal and Kagi--all of which make it quick and easy to distribute software and collect money from customers. The phenomenon of the homebrew coder is not new, of course. For two decades, programmers have distributed their wares as "shareware", initially through dial-up bulletin boards or via disks given away with computer magazines, and later via the internet.